Concept of Learning to Learn and its Context in the Curriculum of Preschool Educational Institutions - Stonkuvienė, Goda (Pedagogika, 2018)
The article actualizes learning to learn as an important component of human activity in the lifelong learning process. The development of learning to learn is already emphasized in the documents regulating the stage of preschool education. In the article the importance of learning to learn for further successful process of child’s learning and its continuity have been substantiated, a problem-based perception of the concept of learning to learn and the components explaining learning to learn have been revealed. It has been emphasized that for the development of learning to learn the focus on this field is important as well as the designing of education in the curriculum of preschool educational institutions. The analysis of the curriculum of preschool educational institutions has revealed the situation of the development of learning to learn that highlighted that the curriculum prepared by institutions reflects a different attitude and preparation to implement the development of this field and achieve the results. It has also been noticed that the curriculum of the institutions lacks a systemic and consistent approach modelling successful development of children’s learning to learn.